Emergency safety for multi-storey public housing in Kuala Lumpur / Nurul Liyana Hanapi, Sabarinah Sh Ahmad and Azli Abd Razak - Hanapi, Nurul Liyana; Sh Ahmad, Sabarinah; Abd Razak, Azli (2019)
Emergency safety factor in buildings is the least achieved element as highlighted in many studies. Poor safety factor could affect a building’s evacuation process as the evacuees are exposed to a greater danger. Thus, this paper focuses on highlighting the common issues raised in public housing and how they affect the evacuation process, through observational study. The findings show that public buildings are highly dependent on passive design approaches to ensure occupant safety during an emergency. Many safety issues are highlighted. Among them, cost and occupant mentality are the main factors contributing to other issue related to safety factor. Cost restricts safety measures, causing problems with maintenance and management, whereas occupants’ behaviour causes maintenance and management efforts to be even more difficult. Further potential studies could focus on ways to mitigate emergency safety issue in buildings as it will not only benefit in terms of safety during an emergency but also increase occupant satisfaction towards public multi-storey residential buildings in Malaysia.